LEGAL SANCTIONS FOR SMOKERS WHO SMOKE IN PUBLIC PLACES IN PHILIPPINES - Jeffrey Kent Epsyke (DUTA BANGSA UNIVERSITY INDONESIA, 2020)
Every person has the right to freedom including smoking as stated in Section 11 of Article II of the 1987 Constitution of the Republic of the Philippines declares that the State values ​​the dignity of every human, person and guarantees full respect for human rights, but the facts on the ground are actually prohibited by smoking. The problem in this study is how the legal sanctions for smokers who smoke in public places. This research method uses a normative juridical approach, with data collection from literature study. The data obtained were analyzed qualitatively. Based on the results of the study it was found that the Philippine Government is only limiting smoking behavior, which is devoted to public places only. The government imposes a fine for smokers up to ₱ 10,000 (US 200) for violations of the smoking ban in public places as prescribed in section 32 of the Tobacco Regulation Act for perpetrators. Enforcement can be performed by members of the Philippine National Police and the local task forces of each city and municipality. Even so, that does not mean that everyone should not smoke. The public may smoke as long as it is done in quiet places and may be done at home.